Community identity, governance, and resilience under agri-environmental shifts in two communities of southwestern Uruguay. Issue 5 (20th October 2019) - Thompson, Diego
ABSTRACT: Since the beginning of the 21 st century, rural communities in southwestern Uruguay have responded differently to agri-environmental challenges created by increases in the production of genetically modified crops. Resilience literature highlights the importance of community identity on local responses, but little has been explored about how economic and political aspects that characterize community identity influence community governance to address local environmental challenges. Based on historical texts, interviews with key informants, participant observation and analysis of reports from public meetings in two communities of southwestern Uruguay, this article explores how community identities were related to whether and/or how communities responded. Results from this comparative study highlight how economic and political aspects influencing community identity could either constraint or facilitate community governance and resilience.